Prevalence patterns of bacterial urinary tract infections among febrile children under-five years of age at Kampala International University Teaching Hospital - Nakalema, Gloria; Ortiz, Yamile A.; Agwu, Ezera (Chemistry and Pharmacy, 2015)
Accurate and reliable diagnosis of UTI in children is critical because they are usually underdiagnosed or over-diagnosed especially in children under five years of age. Antimicrobial susceptibility results are key to effective intervention. This study was done to determine the prevalence patterns of bacterial urinary tract infections among febrile children aged less than 5 years presenting at Kampala International University Teaching Hospital. A hospital-based cross-sectional study was conducted in entry points of the pediatric ward of KIU-TH between December 2020 and March 2021. The study enrolled a total of 350 children 2-59 months by consecutive enrolment. Urinalysis and urine culure was done, clinical and demographic data was collected using questionnaires and data analysed using SPSS version 27 with significance at 95% confidence interval. Out of 350 children studied, 97 (27.7%) had a UTI. E.coli was the most commonly isolated uropathogen (56.7%). There is a high intra hospital prevalence of bacterial UTIs among febrile children under five years of age with with E.Coli as the predominant causative organism.
Keywords: Prevalence patterns; bacterial; urinary tract and infections